Turn-Taking Strategies in the 2024 U.S. Presidential Debate between Donald Trump and Kamala Harris - Ahzami, Farhan; Saehu, Andang; Fauzi, Erfan Muhammad (Journal of English Language and Education, 2025)
Turn-taking is fundamental in political debates, as control of the turn reflects a speaker’s communicative authority. Limited research has compared how different candidates utilize turn-taking strategies to assert control or dominance in presidential debates. This study aims to identify and analyse the turn-taking strategies employed by Donald Trump and Kamala Harris in the 2024 U.S presidential debate using Stenstrom (2014) framework. A total of 130 data points were collected from the ABC News YouTube Channel and analysed using qualitative descriptive methods. Following the steps proposed by Merriam Tisdell (2015). The findings show that Trump predominantly used aggressive interruptive and taking the turn strategies, while Harris tended to apply more structured and holding the turn strategies. The study concludes that turn-taking strategies not only shape the structure and flow of the debate but also reflect each candidate’s dominance in the interaction.